Porphyromonas gingivalis: predominant pathogen in chronic periodontitis - Ramos Perfecto, Donald (2011)
Porphyromonas gingivalis is a gram negative bacillus predominant in chronic periodontitis, multiple virulence factors make it extremely aggressive. In the gingival sulcus find the conditions for growth,interacting with the host produces a slow but steady destruction of periodontal tissue. Its dominance has been considered a risk factor for systemic inflammatory diseases such as myocardial infarction. Although its susceptibility to a variety of drugs makes possible its handling with antimicrobials after mechanical removal of subgingival biofilm. In conclusion this review covers various features of the bacteria, which lead us to the consensus that the pathogen Porphyromonas gingivalis is more relevant in chronic periodontitis,and its presence in various forms of periodontal diseases